TRANSFORMASI PEMBELAJARAN MATEMATIKA: INTEGRASI PROBLEM BASED LEARNING DAN TEACHING AT THE RIGHT LEVEL DALAM PENDEKATAN JOYFUL LEARNING DI SMAN 7 DENPASAR - I Made Surat; I Komang Sukendra (Widyadari, 2025)
This classroom action research aims to improve students’ mathematics learning outcomes through the integration of the Problem Based Learning (PBL) model and the Teaching at the Right Level (TaRL) approach within a Joyful Learning environment. The study was conducted at SMAN 7 Denpasar during the second semester of the 2023/2024 academic year, involving 38 tenth-grade students. The research was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. Initial diagnostic assessments revealed that only 36.8% of students achieved the minimum mastery criteria (score ≥73), indicating a need for differentiated instruction and more engaging learning strategies. In Cycle I, the implementation of PBL and TaRL led to an increase in student mastery to 60.05%. Further refinements in Cycle II resulted in 78.94% of students achieving mastery, surpassing the classical completeness threshold of 75%. The PBL model encouraged students to engage in critical thinking and real-world problem solving, while the TaRL approach allowed instruction to be tailored to students’ actual learning levels rather than grade level. Joyful Learning strategies—such as interactive activities, humor, brain gym, and group collaboration—helped create a positive and motivating classroom atmosphere. The findings demonstrate that the integration of PBL, TaRL, and Joyful Learning is effective in enhancing mathematics achievement and student engagement. This model is recommended as an innovative and adaptive instructional strategy for secondary education.